Effect of filling surface-treated pyrolytic char on resistivity of rubber films - Yamkaya, Pattraporn; Danwanichakul, Duangkamol; Danwanichakul, Panu (Engineering and Applied Science Research, 2015)
In this research, natural rubber (NR) films filled with pyrolytic tire char, carbon black N234 and N330 were compared for their electrical resistivity. The filler loading was varied to be 5, 10, 15, 20 and 25% of dry rubber content. The effect of surfactant which is 2 %w/v sodium dodecyl sulfate (SDS) was also investigated. In the experiments, it was necessary to disperse the pyrolytic char in ethyl alcohol while disperse carbon black (CB) in ammonium hydroxide solution prior to mixing with the rubber latex and the filled NR film was prepared by casting the mixture on a plate. It was found that increasing the amount of pyrolytic char in the NR film could lower its resistivity. The surfactant, SDS, could help better dispersion of both CB and pyrolytic char, thereby decreasing the resistivity. In a separate experiment where hexane vapor was absorbed in NR film without surfactant, in the first 30 seconds, the rate of increasing resistivity of the CB-filled film was not seen as clearly as that of pyrolytic-char-filled film. For the films with surfactant, the slow increase in resistivity of the NR films filled with N330 and pyrolytic char during adsorbing hexane vapor was observed.